Pabna disturbances and the politics of rent : 1873-1885 - Gupta, Kalyan Kumarn Sen. (New Delhi, 1974)
The uprising in 1873 of ryots in Pabna against the permanently settled landlords is a significant event in the late 19th century socioeconomic history of Bengal. Con ducted under the aegis of a powerful and efficient agrarian league the movement created the conditions for similar up risings in other parts of eastern and central Bengal (now Bangladesh). Patterned on the Pabna model these move ments gradually took the aspect of a widespread and popular protest against the late 19th century forms of landlordism in the cash crop producing areas of Bangladesh. These forms are shown in later chapters to represent a stage of change in the pattern of ownership and of its impact on the tenantry which developed under 19th century colonialisation of the growth of a desire on the part of some landlords to hold their estates, untrammelled by even conventional rules and regulations for protection of their tenantry. This stage re presents what may be called 'high landlordism'. The usage here is analogous to haute bourgeoisie, i.e. that stage in the development of bourgeoisie in which sections of it developed enough control over capital to deal as they wished with the working class. High landlords or those who aspired to be such behaved in the same way with working peasantry. It is my contention that such practices in Pabna set the stage for the different peasant movements in Bangladesh in the late 19th century.
Keywords: Rent